ROBUST OPTICAL AUTOFOCUS SYSTEM UTILIZING NEURAL NETWORKS APPLIED TO AUTOMATED MULTIWELL PLATE STORM MICROSCOPY - Lightley,J; Görlitz,F; Kumar,S; Kalita,R; Kolbeinsson,A; Garcia,E; Alexandrov,Y; Bousgouni,V; Wysoczanski,R; Barnes,P; Donelly,L; Bakal,C; et al. (2021)
We present a robust, low-cost neural network-based optical autofocus system that can operate over a range of ±100µm with submicron precision, enabling automated high-content super-resolved imaging with a 1.3 NA objective lens.